Radiocarbon ages of sediment core GeoB9506-1 - Barragán-Montilla, Sofía; Mulitza, Stefan (PANGAEA, 2025)
The data sets contain the radiocarbon ages measured from 16 planktic foraminifera samples of gravity core GeoB9506-1. The samples from the gravity cores were obtained from working/archive halves at the GeoB Core Collection at the MARUM – Center for Marine Environmental Sciences, University of Bremen, Germany. 10 cc of sediment was collected at different depths, and the samples were (1) washed with deionized water through a 63 µm sieve, then (2) dried for less than 24 hours at 45°C, and (3) dry sieved through 63 µm, 125 µm, 150 µm, and 250 µm. Finally, the washed sediment with a size >150 µm was used to retrieve at least 300 specimens of planktic foraminifera including Globigerinoides ruber and Globigerinoides sacculifer. The radiocarbon measurements were carried out at the MICADAS laboratory at the Alfred Wegener Institute in Bremerhaven (https://www.awi.de/en/science/geosciences/marine-geochemistry/micadas.html).
Keywords: North Atlantic; NW Africa; planktic foraminifera; radiocarbon age